Green Retail and Consumer Preferences for Sustainable Products - Andi Wahyuni Syam; M Nur Rahmat Achdar HT HT; Nasaruddin Nasaruddin; Anugrahwati Anugrahwati; Ana Andania (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
This study aims to examine consumers' knowledge, awareness, and behavior regarding green retail and sustainable products in Bone Regency. Using a qualitative approach through in-depth interviews with consumers in rural areas, the study found that consumer literacy regarding sustainable products remains very limited, and many do not even understand the specific meaning of environmentally friendly products. Consumer choices are generally based on price, practicality, and availability, whereas sustainability considerations or green labels are secondary. The influence of social factors, such as family, friends, and the media, on green consumption behavior remains weak. Additionally, access to environmentally friendly labeled products in local markets remains very limited, and higher prices often constitute the primary barrier to adopting sustainable consumption behavior. These findings highlight the need for more practical environmental education, the expansion of the distribution of green products to rural areas, and tangible incentives from the government and businesses to enhance the competitiveness of green products in the local market. This study also recommends collaboration among the government, producers, retailers, and local communities to accelerate changes in consumer behavior and strengthen the green retail ecosystem in rural Indonesia